Survival of an infant with homozygous surfactant protein C (SFTPC) mutation. Issue 3 (17th December 2013) - Arıkan‐Ayyıldız, Zeynep; Caglayan‐Sozmen, Sule; Isık, Sakine; Deterding, Robin; Dishop, Megan K.; Couderc, Remy; Epaud, Ralph; Louha, Malek; Uzuner, Nevin
Summary Lung diseases caused by surfactant protein C (SFTPC) mutations are inherited as autosomal traits with variable penetrance and severity or as sporadic disease caused by a de novo mutation on one allele. Here, we report the case of a child surviving with a homozygous surfactant protein C mutation after aggressive clinical management unlike his six siblings who died in infancy. This presentation raises the suspicion of an autosomal recessive inheritence that is discussed in this report. Pediatr Pulmonol. 2014; 49:E112–E115. © 2013 Wiley Periodicals, Inc.